2016
DOI: 10.1007/s10530-016-1203-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving the containment of a freshwater invader using environmental DNA (eDNA) based monitoring

Abstract: On-ground management actions targeting invasive and/or native species are often undertaken based on incomplete and biased distribution data for the species of interest. Once an invasive species becomes established, containment can provide an effective management option to conserve native biodiversity only if it is implemented beyond the outer distribution limits of the species of interest. Determining these outer distribution limits is currently difficult for freshwater fish species because of the low sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…; Laramie, Pilliod & Goldberg ; Bylemans et al . ). Furthermore, it has been suggested that the absolute abundance of mitochondrial (mt‐) eDNA fragments can be used to determine the reproductive status of populations (Spear et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Laramie, Pilliod & Goldberg ; Bylemans et al . ). Furthermore, it has been suggested that the absolute abundance of mitochondrial (mt‐) eDNA fragments can be used to determine the reproductive status of populations (Spear et al .…”
Section: Introductionmentioning
confidence: 97%
“…Environmental DNA-based species detection is a relatively new technique which is particularly useful for detecting aquatic species at low densities (Ficetola et al 2008;Thomsen et al 2012a). The sensitivity of this technology can be used to improve presence/absence data for cryptic species (Dejean et al 2012;Thomsen et al 2012b;Sigsgaard et al 2015) and accurately delineate the distribution of species (Jerde et al 2011;Laramie, Pilliod & Goldberg 2014;Bylemans et al 2016a). Furthermore, it has been suggested that the absolute abundance of mitochondrial (mt-) eDNA fragments can be used to determine the reproductive status of populations (Spear et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…bluegill sunfish ( Lepomis macrochirus ) (Takahara et al 2013). This increased effectiveness, combined with relatively low financial costs and reduced impact on the environment, demonstrates that eDNA methodologies have high potential for enhancing the management of invasive fish species (Rees et al 2014; Bylemans et al 2016). Applications so far have included distribution assessments (Takahara et al 2013; Keskin 2014), monitoring surveys on invasion fronts (Jerde et al 2013; Adrian-Kalchhauser and Burkhardt-Holm 2016) and the evaluation of population eradication attempts (Dunker et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of eDNA to detect and monitor invasive species at low densities has numerous advantages over traditional techniques, Sampling point 1 2 3 4 5 6 7 8 9 10 P1 PCR 0 0 0 0 3 0 0 0 0 0 P1 qPCR1 2 3 3 2 3 3 2 1 0 3 P1 qPCR2 0 0 0 2 0 0 1 0 0 1 P2 PCR 0 1 0 1 0 0 1 1 1 1 P2 qPCR1 1 3 0 2 0 3 2 1 3 3 P2 qPCR2 1 0 0 2 0 1 0 0 0 0 P3 PCR 0 1 0 2 1 1 0 0 0 1 P3 qPCR1 0 2 0 3 3 3 0 (Evans, Shirey, Wieringa, Mahon, & Lamberti, 2017;Jones, 2013;Tucker et al, 2016). For example, eDNA from European weather loach (Misgurnus fossilis) and redfin perch (Perca fluviatilis) was detected at sites where fishing had previously failed to find these species (Bylemans, Furlan, Pearce, Daly, & Gleeson, 2016;Sigsgaard, Carl, Møller, & Thomsen, 2015). P. parva has a small size, and trapping can on occasions be unsuccessful, particularly during the early life stages…”
Section: Discussionmentioning
confidence: 99%